Analysis of Laboratory Videos of Science Teacher Candidates with Many-Facet Rasch Measurement Model - Ahmet Volkan Yuzuak; Sinan Erten; Yilmaz Kara (Journal of Education in Science, Environment and Health)
Aim of the present study is to analyze science teacher candidates’ laboratory videos by using Many-facet Rasch model. Survey method was used in the study. The study was conducted in 2017-2018 academic year spring semester. Rasch model’s surfaces are respectively: 9 juries, 13 science activities and 19 criteria. FACETS program was used for data analysis. Findings reveal that laboratory video, which was coded as SA8, was found to be the most successful and SA1 coded video was found the most unsuccessful with respect to criteria. The simplest articles which science teacher candidates were subjected are “introducing yourself”, “using proper costume”, “appropriate time” and the articles for which the science teacher candidates are constrained mostly “sound-supporting effect”, “writing effect”, “warning for security precautions”.Jury numbered 3 or coded as J3 is “the most lenient” and scorer numbered 2 is “the severest” when juries are sequenced from the most lenient. Moreover, it could be said that, some of the jury members were extremely severe or lenient against some science activities according to bias analysis.